Potential 2050 distributions of World Terrestrial Ecosystems from projections of changes in World Climate Regions and Global Land Cover - Roger Sayre; Charlie Frye; Sean Breyer; Patrick R. Roehrdanz; Paul R. Elsen; Kevin Butler; Clint Brown; Jill Cress; Deniz Karagulle; Madeline Martin; Florencia Sangermano; Regan L. Smyth; et al. (Global Ecology and Conservation)
The urgency to address ecosystem loss is paramount, as both land use change and climate change will continue to rapidly alter and degrade natural ecosystems and reduce the many services they provide. To support conservation actions that mitigate impacts from these dual threats, we have developed potential World Terrestrial Ecosystem (WTE) distributions for 2050 following IPCC best practice guidelines. This projection of ecosystem distributions builds on the previously released 2015 WTEs, a snapshot of the distribution and conservation status of 431 terrestrial ecosystem types defined as distinct combinations of 18 global climate regions, 4 global landform classes, and 8 global vegetation/land cover classes. Extending that work herein, we modeled the potential 2050 WTE distributions based on projections of five CMIP6 general circulation models (GCMs) and one global land cover change model, determined for three shared socioeconomic pathway (SSP) scenarios. The climate region modeling included projections for 2050 for both mean annual temperature and mean annual aridity. Model agreement for changes to WTEs was generally high, particularly for temperature projections. Widespread changes in ecosystem classes due to shifts in climate settings and/or land cover between 2015 and 2050 were projected, with both the magnitude and specific geography of projected change largely governed by the SSP scenario. For the three SSP scenarios (sustainable development, regional rivalry, and fossil-fueled development), geographic changes in climate setting (temperature, aridity, or both) and/or changes in vegetation/land cover are projected for 29 %, 36 %, and 39 % of Earth’s terrestrial surface, respectively. These changes occur in areas where 31 %, 36 %, and 41 % of the global population lives. Projected changes in ecosystem distributions related to temperature change are approximately an order of magnitude greater than for aridity change. By offering insight into potential ecosystem changes, this new resource is intended to facilitate conservation planning and priority setting aimed at improved conservation of biodiversity and ecosystem services.